PERANCANGAN MOTION GRAPHIC PROMOSI WISATA ALAM KOTA PADANG - Andhika firsenda; syafwan syafwan (Universitas Negeri Padang, 2020)
West Sumatera have a great potential in the field of tourism. The potential is very diverse and is not inferior to other regions. One area that has great tourism potential in West Sumatera is Padang City. The city of Padang has a variety of natural beauty such as mountains, rivers, beaches, and hills. Because there are a lot of nature tourism in Padang city and the magnitude of the community for recreation, as well as the wishes of the Departement of Tourism and Culture of Padang, The media needs to be made with the tittle “Designing motion graphic for the promotion of nature tourism in Padang”.The design of motion graphic regarding the promotion of natural tourism in Padang using glass boxes and black boxes method. The Result of motion graphic in the form of H264 or MP4 format video with HD 720P resolution 25fps and promoted on social media. In addition to the main media, this design also uses supporting media in the form of posters, x-banners, t-shirts, mugs, stickers, totebags, dan key chains. The Result of this motion graphic design, in order to promote natural of tourism in the city of Padang. The motion graphic result are also utilized by the departement of tourism and culture of Padang to support the promotion of nature tourism that is more creative and innovative.Keywords : Tourism, Motion Graphic, City of Padang